2014
DOI: 10.5815/ijcnis.2014.08.04
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Response of Query in Semantic Web

Abstract: Abstract-Today, XML has become one of the important formats of saving and exchanging data. XML structure flexibility enhances its use, and the content of XML documents is increasing constantly. As a result, since file management system is not able to manage such content of data, managing XML documents requires a comprehensive management system. With the striking growth of such databases, the necessity of accelerating the implementing operation of queries is felt. In this paper, we are searching for a method th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Jones et al 2006 [12], have proposed a model for generating queries to be suggested based the concept of query rewriting. A query is rewritten into a new one either by means of query or phrase substitutions [13] or using tools [14].…”
Section: Related Workmentioning
confidence: 99%
“…Jones et al 2006 [12], have proposed a model for generating queries to be suggested based the concept of query rewriting. A query is rewritten into a new one either by means of query or phrase substitutions [13] or using tools [14].…”
Section: Related Workmentioning
confidence: 99%